Analisis Genetik Gen Leptin Berdasarkan Sekuen DNA GenBank dan Asosiasinya dengan Reproduksi Ternak Babi - Cynthia Dewi Gaina; Filphin Adolfin Amalo; Yustinus O. P. Wuhan (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2023)
A candidate gene suspected of affecting pigs' reproductive traits is known as the leptin (LEP) gene. Based on the information found in Leptin GenBank's DNA sequence database, this research aimed to determine single nucleotide polymorphisms (SNPs) and changes in nucleotides and phylogenetic trees in pigs. The data from NCBI GenBank was used to obtain three different DNA sequences of the Leptin gene in pigs. The DNA sequence data for leptin were aligned using BioEdit to establish the sites of SNPs and alterations in nucleotides. A phylogenetic tree was constructed using Mega X. DNA sequences were, and the pig LEP gene was sequenced resulted in 11 SNPs. These findings are based on the sequence regions. The phylogenetic analysis revealed that the sequence of the Leptin gene in pigs (Sus scrofa) clustered more closely with that of goats (Capra hircus) than it did with the sequence of the LEP gene among the cattle (Bos taurus and Bos indicus). The outcomes of this study can serve as a basis for more investigation into the connection between the LEP gene SNP and reproductive traits in pigs as one of potential genes for molecular selection.